Internalized Ageism and Other Barriers to Purpose in Later Life: Protocol for a Qualitative Study - Sonsoles Valdivia-Salas; Alejandra Chulián (International Journal of Qualitative Methods)
The aging process presents a complex interplay of physiological, psychological, and social transformations, shaping individual experiences in profound ways. This research protocol outlines a qualitative study exploring the intersection of purpose in later life, internalized ageism and other barriers to purpose, and psychological flexibility among older adults. Internalized ageism, encompassing negative stereotypes, prejudice, and self-discriminatory practices based on age, can significantly impact an individual’s sense of self and well-being. Simultaneously, the pursuit and maintenance of purpose, a driving force behind motivation and engagement, becomes particularly salient in later life as individuals navigate changing roles and responsibilities. Psychological flexibility, defined as the ability to adapt to changing circumstances and maintain goal-directed behavior, may play a crucial role in mitigating the negative effects of internalized ageism and fostering a sense of purpose in late life, although research is scarce. This study aims to delve into the lived experiences of older adults, examining how internalized ageism influences their sense of purpose and the role of psychological flexibility in navigating these challenges. By employing qualitative methods, we seek to identify potential markers of psychological in/flexibility in later life that could inform the development of assessment measures at this age stage.